2020
DOI: 10.1002/job.2427
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic test of the differential pathways linking ethical leadership to normative conduct

Abstract: We test how ethical leadership influences normatively (in)appropriate work behavior through distinct mediating pathways, including one's exchange relationship with the leader, ethical culture, and identification with the organization. Our study also controls for transformational leadership as a predictor and trust in leader as a nonhypothesized alternative mechanism. We test our hypotheses using metaanalytic structural equation modeling based on our meta-analysis of 301 independent samples (N = 103,354) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 221 publications
(211 reference statements)
4
88
0
Order By: Relevance
“…The job descriptive index (JDI) [ 27 ] was adapted and utilized to measure task satisfaction. The JDI consists of 18 adjective checklist items (e.g., “fascinating,” “satisfying,” “frustrating”) which participants answer with a “yes,” “no,” or “?” if they were unsure whether the task fit the adjective description.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The job descriptive index (JDI) [ 27 ] was adapted and utilized to measure task satisfaction. The JDI consists of 18 adjective checklist items (e.g., “fascinating,” “satisfying,” “frustrating”) which participants answer with a “yes,” “no,” or “?” if they were unsure whether the task fit the adjective description.…”
Section: Methodsmentioning
confidence: 99%
“…The positive relationship between certain aspects or styles of leadership and their relationship with job satisfaction has a long-standing history, and has been demonstrated in multiple contexts and with multiple dimensions of leadership. For example, recent meta-analyses confirm the importance of leader emotional intelligence on subordinates’ satisfaction [ 25 ], leader behaviors (consideration and initiating structure) on the job satisfaction of nurse faculty [ 26 ], and ethical leadership on job satisfaction [ 27 ]. Two articles reviewed above [ 3 , 5 ] suggested that employee job satisfaction is or should also be an outcome from authentic pride of leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ethical leaders discusses how they influence their followers through social exchange and social learning processes (Brown et al, 2005). Followers of ethical leaders may feel that they need to reciprocate the positive behavior that is offered to them (Brown and Mitchell, 2010;Peng and Kim, 2020). Researchers advocating this perspective build on theorizing by Bandura (1986), who posits that a learning process can occur not only via direct experience but also via vicarious experience, which is a learning process by observing others' behaviors and their consequences.…”
Section: The Effect Of Ethical Leadership On Corruptionmentioning
confidence: 99%
“…Since the presentation of this definition, the descriptive and social scientific line of inquiry on ethical leadership has gained momentum in the general management literature, with a multitude of empirical – often quantitative survey based – studies focusing on the antecedents (such as moral identity and emotional stability), mechanisms (such as organizational ethical climate and team cohesion), and consequences (such as followers’ commitment and organizational citizenship behaviour) of ethical leadership ( Bedi et al, 2016 ; Ko et al, 2018 ; Peng & Kim, 2020 ). Emphasis has thereby mainly been put on follower perceptions of the leaders’ characteristics and behaviours.…”
Section: Ethical Leadership In Sport: a Descriptive Perspectivementioning
confidence: 99%